Fiqih and Progressive Law: Study of Inequality and Racial Issues in America - Anshor, Ahmad Muhtadi (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2021)
Racial issues and gaps in the US are a phenomenon that the world is witnessing, where intimidation against minority groups is often heard, and this act certainly contravenes the values of appropriateness and human values people of all races highly respect. This research is literature-based in which the data was analyzed in descriptive method based on content analysis. This research aims to reveal the racial issues in the US seen from the perspective of Fiqh and progressive law. The findings of this research imply that this phenomenon contravenes the fundamental principles of fiqh and progressive law.